BERNOULLI QUARTIC GENERATION BY AN ORIGINAL - Iulian POPESCU; Mirela CHERCIU (Fiabilitate şi Durabilitate)
The paper is based on a geometrical method for generating Bernoulli Quartic anddesign a mechanism that can generate it. The found mechanism is R-RTT-RTR - Triad of order 3.The analytical equations are obtained through the outlines method and the desired curve isobtained using a computer program. The curve is generated and the functioning of the generatingmechanism is analyzed on the basis of some diagrams